Electrolytic Preparation of Mg-La Alloy in Chloride Molten Salt: Effect of Electrolyte Composition. Issue 7 (July 2015) - Shidong, Wang; Quan, Li; Xiushen, Ye; Qingguo, Sun; Zhijian, Wu
Abstract: Mg-La alloys were prepared by potentiostatic electrolysis in the molten salt system of MgCl2 -LaCl3 -KCl. The effects of electrolyte composition on average electrolysis current, current efficiency, and compositions of the alloy products were investigated. X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) were used to characterize the Mg-La alloy product. The average electrolysis current is found to gradually decrease with the increase of the LaCl3 content in the initial electrolyte due to the lower conductivity of LaCl3 as compared to that of MgCl2 . A high current efficiency over 90% can be obtained when the electrolyte composition is KCl (65wt%), MgCl2 (20wt%−15wt%), and LaCl3 (15wt%–20wt%). The compositions of the obtained Mg-La alloys can be adjusted by changing the electrolyte composition.